Decision Support System Recommended for Position Increased at PD. Air Minum Jaya By Using SMART Method - Rudianto, Rudianto (Universitas Medan Area, 2019)
Employees are one of the human resources that are very important in determining the success of the company's work. There fore the company must appoint employees into one of the positions according to the expertise desired by the company. There are still many managers to appoint their employees to only see how long they work without being supported by adequate expertise. So that the appointment of employees by managerial is subjective. For this reason, it is necessary to process employee assessment data that can help make it easier for a boss and the Payroll section to take a decision to recommend employees to take office. The method used to solve the problem of recommendation for promotion for employees by using the SMART method (Simple Multi Attribute Rating Technique) is a multi-attribute decision-making method used to support decision making in choosing between several alternatives. The criteria used in calculating the assessment are professional criteria, cooperation, leadership, innovation and ethics at work. Judging from the managerial aspects, the assessment can be developed with other criteria according to the needs of the company